Recurrent Drought Conditions Enhance the Induction of Drought Stress Memory Genes in Glycine max L. - Kim, Yeon-Ki; Chae, Songhwa; Oh, Nam-Iee; Nguyen, Nguyen Hoai; Cheong, Jong-Joo (Frontiers in Genetics, 2020)
Plants remember what they have experienced and are thereby able to confront repeated stresses more promptly and strongly. A subset of the drought responsive genes, called stress memory genes, displayed greatly elevated levels under recurrent drought conditions. To screen for a set of drought stress memory genes in soybean (Glycine max L.), we designed a 180K DNA chip comprising 60-bp probes synthesized in situ to examine 55,589 loci. Through microarray analysis using the DNA chip, we identified 2,162 and 2,385 genes with more than 4-fold increases or decreases in transcript levels, respectively, under initial (first) drought stress conditions, when compared with the non-treated control. The transcript levels of the drought-responsive genes returned to basal levels during recovery (watered) states, and 392 and 613 genes displayed more than 4-fold elevated or reduced levels, respectively, under subsequent (second) drought conditions, when compared to those observed under the first drought stress conditions. Gene Ontology and MapMan analyses classified the drought-induced memory genes exhibiting elevated levels of transcripts into several functional categories, including those involved in tolerance responses to abiotic stresses, which encode transcription factors, protein phosphatase 2Cs, and late embryogenesis abundant proteins. The drought-repressed memory genes exhibiting reduced levels of transcripts were classified into categories including photosynthesis and primary metabolism. Co-expression network analysis revealed that the soybean drought-induced and -repressed memory genes were equivalent to 172 and 311 Arabidopsis genes, respectively. The soybean drought stress memory genes include genes involved in the dehydration memory responses of Arabidopsis.